Spectrum of Chest Computerised Tomography (CT) findings of Covid 19 in Indian Population - Boini Shravya1 , Vikas Chennamaneni2 , Vamshi Kiran Diddy3 , Momin Sayed Kashif4 (Perspectives In Medical Research, 2021)
Background: To analyze the chest computed tomography (CT) features in patients with coronavirus disease 2019 (COVID-19) pneumonia. Methods: This was a prospective descriptive study comprising 202 consecutive reverse transcriptase polymerase chain reaction (RT-PCR) positive patients who underwent CT chest. For 25 patients, follow-up CT scans were obtained. The CT images were evaluated for the number, type and distribution of the opacity, and CT severity scoring was done Results: Among the total study cohort of 202 patients, 152 were males and 50 were females .From July 07, 2020, to september07, 2020, totally 202 laboratory-confirmed patients with COVID-19 underwent chest CT. For 25 patients, follow-up CT scans were obtained. The CT images were evaluated for the number, type and distribution of the opacity, and the affected lung lobes. Furthermore, the initial CT scan and the follow-up CT scans were compared. Results were patients (98.5%) had two or more opacities in the lung and 3 (1.5%) patients has negative chest CT. 183 (90.6%) patients had only ground-glass opacities; 13 patients (6.4%) had ground-glass and consolidative opacities; and 3 patients (1.5%) had only consolidation. A total 192 of patients (96.5%) showed two or more lobes involved. The opacities tended to be both in peripheral and central 7 (3.5%) or purely peripheral distribution 192 (96.5%). 177 patients (88.9%) had the lower lobe involved.8 patients showed complete resolution of lung findings. Conclusion: In this study population, the typical CT features of COVID 19 pneumonia are ground glass opacity with or without consolidation, which is patchy and peripheral, predominantly in lower lobes.